Things in Culture, Culture in Things - Kannike, Anu (Approaches to Culture Theory, 2013)
This volume addresses the dynamics of materiality over time and space. In cross-cultural, multi-temporal and interdisciplinary studies the authors examine how things gain meaning and status, generate a multitude of emotions, and feed into the propagation of myths, narratives and discourses. The book is divided according to four themes: soft objects, stoic stories, consuming and the collectable, and waste and technologies. The first section discusses the meanings of the lived environment on the individual and national levels. The second section provides specific examples on the role of things in identity construction. The third section focuses on historical and contemporary aspects of consumption and collecting. The phenomena under scrutiny in the fourth section are moral dilemmas associated with and representations of dirt/waste and advancements in science and technology. Presenting diverse case studies of material culture, the volume points to rich interdisciplinary approaches in cultural theory.